Penggunaan Teori Belajar Behaviorisme Dalam Meningkatkan Pemahaman Konsep Biologi Di Sekolah Menengah Atas - Adinda Carissa Maharani; Fairuz Najla Rachmadani; Indana Zulfa; Muhammad Rafi Alfarizi; Ade Suryanda (Pragmatik : Jurnal Rumpun Ilmu Bahasa dan Pendidikan, 2024)
This article discusses the use of behaviorism learning theory to increase the understanding of biological concepts in high school. The method used in this article is a literature study or literature review. The research results reveal that the use of behaviorist learning theory increases understanding of biological concepts through providing regular stimuli so that appropriate responses are obtained. The use of flipbook media as a behavioristic approach also increases students' motivation in learning, thereby influencing learning outcomes or achievement. It can be concluded that the use of behaviorism learning theory can increase understanding of biological concepts in high school.